Information management in IoT cloud-based tele-rehabilitation as a service for smart cities: Comparison of NoSQL approaches. (February 2020) - Celesti, Antonio; Lay-Ekuakille, Aimé; Wan, Jiafu; Fazio, Maria; Celesti, Fabrizio; Romano, Agata; Bramanti, Placido; Villari, Massimo
Highlights: Recent advancements in ICT have sped up the development of new healthcare services. We focus on the Tele-Rehabilitation as a Service (TRaaS) concept. Remote rehabilitation big data need to be processed in hospital Clouds. We used the Lokomat data format as sample. We compared the performances of four of the major NoSQL DBMS solutions. Abstract: Nowadays, recent advancements in ICT have sped up the development of new services for smart cities in different application domains. One of these is definitely healthcare. In this context, remote patient monitoring and rehabilitation activities can take place either in satellite hospital centres or directly in citizens' homes. Specifically, using a combination of Cloud computing, Internet of Things (IoT) and big data analytics technologies, patients with motor disabilities can be remotely assisted avoiding stressful waiting times and overcoming geographical barriers. This paper focuses on the Tele-Rehabilitation as a Service (TRaaS) concept. Such a service generates healthcare big data coming from remote rehabilitation devices used by patients that need to be processed in the hospital Cloud. Specifically, after a feasibility analysis, by using a Lokomat dataset as sample, we measured and compared the performances of four of the major NoSQL DBMS(s) demonstrating that the document approach well suits our case study.